CODE-SWITCHING AMONG STUDENTS OF DHAKA UNIVERSITY, BANGLADESH: A STUDY ON RESIDENTIAL STUDENTS - Islam, Md. Sadequle (Elite : English and Literature Journal, 2018)
This paper focuses on an analysis of Bangla, English and Hindi code switching among the students of Dhaka University, Bangladesh. Based on the empirical data from questionnaire filled up by the students of two male and two female residential halls of Dhaka University, this paper aims to analyze the frequency and prototypes of code switching. It also presents a brief overview on exploring the factors that influence or encourage code switching and also the attitudes of the students towards the contemporary trend of code switching and its impact on their mother tongue Bangla. After collecting the data, they are transcribed, tabulated and analyzed by following quantitative method in terms of the research objectives. Overall findings indicate that in spite of having a negative attitude towards code switching, students prefer to switch Bangla-English and Bangla-Hindi codes with the friends in the informal discussions and while using social media.